The Influence of Price and Product Quality on Purchasing Decisions of EIGER Products - Deden Sofyan Hamdani; Zaky Ralf Mulya Andriana; Neng Susi Susilawati Sugiana; Tuti Sulastri (Jurnal Komputer Bisnis, 2025)
This study explores the influence of price and product quality on purchasing decisions of EIGER products, a leading Indonesian outdoor brand. The primary objective is to analyze how consumers interpret and respond to EIGER's pricing strategies in relation to their perception of product quality. The research employs a qualitative method involving 20 purposively selected respondents who have experience purchasing EIGER products. Through in-depth interviews, the study identifies key factors that shape consumer decisions, such as perceived durability, brand image, and value for money. Findings reveal that while EIGER enjoys strong brand recognition, there is a discrepancy between consumer expectations and actual product performance, particularly in areas such as material durability and pricing fairness. Several respondents expressed skepticism toward EIGER's premium pricing, citing inconsistent quality and lack of after-sales support. These insights suggest that EIGER must realign its quality standards with consumer expectations to maintain brand loyalty and competitive advantage. The practical implications include the need for improved quality control and more transparent communication strategies regarding product features and benefits. This study is unique in its focus on a national brand in an emerging market, offering localized insights that are often overlooked in global literature.